Evaluasi Kinerja Keuangan Daerah Melalui Analisis Perencanaan Dan Penganggaran Pembangunan Daerah - Ella Priskila; Alexandra Hukom (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to evaluate the financial performance of regions through analysis of regional development planning and budgeting. The method used is literature review and analysis of regional financial data. The data used are regional financial data consisting of regional revenue and expenditure budgets, as well as actual revenue and expenditure. The results show that the evaluation of regional financial performance can be done by measuring the extent to which the financial performance of the region achieves the planned regional development goals. Analysis of regional development planning and budgeting can be used as a tool to evaluate regional financial performance as it can reveal how far the budget that has been prepared and executed can achieve regional development goals. In this study, it is concluded that the evaluation of regional financial performance through analysis of regional development planning and budgeting can be an effective tool in improving regional financial performance and achieving regional development goals.